2021
DOI: 10.1136/jitc-2020-002198
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell composition and functional marker dynamics from multiplexed immunohistochemistry to predict response to neoadjuvant chemotherapy in the WSG-ADAPT-TN trial

Abstract: BackgroundThe association of early changes in the immune infiltrate during neoadjuvant chemotherapy (NACT) with pathological complete response (pCR) in triple-negative breast cancer (TNBC) remains unexplored.MethodsMultiplexed immunohistochemistry was performed in matched tumor biopsies obtained at baseline and after 3 weeks of NACT from 66 patients from the West German Study Group Adjuvant Dynamic Marker-Adjusted Personalized Therapy Trial Optimizing Risk Assessment and Therapy Response Prediction in Early Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…5h ) in recurrent tumors. A number of recent studies postulate that such alterations in the tumor immune microenvironment are in response to NST and are likely to have predictive value in treatment outcomes 43 45 . Secondly, our findings suggest that the immunologically quiescent primary tumors which are at risk of post-pCR relapse could benefit from the early use of immune-oncologic agents either alone or in combination with NST.…”
Section: Discussionmentioning
confidence: 99%
“…5h ) in recurrent tumors. A number of recent studies postulate that such alterations in the tumor immune microenvironment are in response to NST and are likely to have predictive value in treatment outcomes 43 45 . Secondly, our findings suggest that the immunologically quiescent primary tumors which are at risk of post-pCR relapse could benefit from the early use of immune-oncologic agents either alone or in combination with NST.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with either chemotherapy or HER2 targeted therapies lead to increase of markers associated with cellular immunity, except for a study [75], which demonstrated that chemotherapy globally downregulated the expression of immune markers. Compared with baseline, increased infiltration of CD8+ [60,77], FOXP3+ [60], CD8+PD1+ [61] and PD-L1+ [61] was noted, while CD3+KI67+ [60] cells decreased. Interestingly, intra-tumoral spatial distribution of T cells also changed, with CD3+ and CD8+ T cells being recruited closer to cancer cells, either in tumoral [60,61,77] or proximal stromal compartments [60].…”
Section: Inter-patient Spatial Heterogeneity: Characterization Of Spa...mentioning
confidence: 84%
“…Compared with baseline, increased infiltration of CD8+ [60,77], FOXP3+ [60], CD8+PD1+ [61] and PD-L1+ [61] was noted, while CD3+KI67+ [60] cells decreased. Interestingly, intra-tumoral spatial distribution of T cells also changed, with CD3+ and CD8+ T cells being recruited closer to cancer cells, either in tumoral [60,61,77] or proximal stromal compartments [60]. In summary, these studies demonstrate that multiplex methods can be used to evaluate the dynamic changes of TIME, under the pressure of neoadjuvant therapy.…”
Section: Inter-patient Spatial Heterogeneity: Characterization Of Spa...mentioning
confidence: 84%
See 2 more Smart Citations